Synergy of tourism and agriculture in increasing the exchange rate of farmers in Tabanan District: a critical review - Bagus Arya Kusuma; Ni Nyoman Yuliarmi; Putu Ayu Pramitha Purwanti (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study aims to analyze the synergy between tourism and agriculture to increase the exchange rate of farmers in the Tabanan Regency area. A literature review approach with a focus on critical review was used in this study. Based on previous research, the study looked at how the Tabanan district's policies affect how tourism and farming work together. The components analyzed are the rationalization and realization of policy implementation related to the analyzed review. This research is a critical literature review to assess, compare, and compile strategy characteristics. The results obtained from the synergy between tourism and agriculture in Tabanan Regency have the potential to be implemented to increase the farmer exchange rate. The idea of mutualism between the two sectors is expected to help tourist villages grow. Improving the size and quality of tourist villages, with the help of local governments, will lead to changes affecting farmers' incomes and exchange rates. They will be able to see the well-being of their farmers. Factors that must be realized to make this synergy concept a success include: 1) the Tabanan Regency Government can facilitate the development of tourist villages; 2) farmers are expected to be open to accepting synergy models of work with the tourism sector, and 3) tourism actors assist farmers in identifying local potentials that have economic value. The policy will likely lead to more and better tourist villages, raising farmers' exchange rates and improving their lives. In conclusion, combining tourism and agriculture makes much sense. The rationalization of policies that local governments and farmers work on can help increase farmers' exchange rates locally and regionally.